Screening of antimicrobial and antioxidant activities of endophytic actinomycetes isolated from rhizophora mucronata and sonneratia caseolaris - Mesta, Sunita C. (International Journal of Pharmaceutical & Biological Archive, 2017)
The aim of the present study was to evaluate the antimicrobial and antioxidant activity of crude extract or secondary metabolites of Endophytic actinomycetes species isolated from two mangrove plants collected from Cortalim, Goa, India. The plant parts were surface sterilized and plated on Oat meal agar supplemented with 10% sea water and actinomycetes isolates were obtained. Antimicrobial activity was studied by cross streak method and agar diffusion method by using six bacteria and four fungi. The potent isolates were subjected for Fermentation and the extracellular metabolites were extracted by using the ethyl acetate solvent and were subjected for antimicrobial screening. Isolate RO 7, RO 11 showed more inhibition against all the tested bacteria and Isolate RO 9 showed both antibacterial and antifungal activity. Antioxidant activity was done by DPPH radical scavenging assay. The results showed dose dependant antioxidant activity. The ethyl acetate extract RO 7 showed 94.11% inhibition at 100Î¼g/ml followed by RO 11 and RO 9 showing 64.70% and 61.17% inhibition at 100Î¼g/ml and the inhibition was compared with standard antioxidant ascorbic acid which showed 100% inhibition at 100Î¼g/ml. The finding of the present study shows that endophytic actinomycetes could be potential natural source of antioxidants and antibiotics.